Psychological impact of COVID-19 pandemic on healthcare workers and strategies to mitigate them - MD. Abu Bashar; Nazia Begam (Wolters Kluwer Medknow Publications, 2020)
The outbreak of a novel coronavirus starting from December 2019 and reaching pandemic proportions has raised concerns as to the ability of current protective measures and the health-care system to handle such a threat. Health-care workers may experience considerable psychological distress as a result of the COVID-19 pandemic due to providing direct patient care, vicarious trauma, quarantine, or self-isolation.